Dynamic Image-Based Visual Servoing of Monocular Camera Mounted Omnidirectional Mobile Robots Considering Actuators and Target Motion via Fuzzy Integral Sliding Mode Control - Lee, Sanghyob; Chwa, Dongkyoung (IEEE Transactions on Fuzzy Systems, 2021)
In this article, an image-based visual servoing (IBVS) method for monocular camera mounted three-wheeled omnidirectional mobile robots (OMRs) is proposed using a novel fuzzy integral sliding mode control (FISMC) method. Most of the existing studies for IBVS of wheeled mobile robots (WMRs) have focused only on kinematics, even though no consideration for the OMR dynamics, actuators, and target motion can lead to much degraded performance. Accordingly, a camera mounted OMR is first modeled considering the OMR dynamics, actuator dynamics, and disturbance effects of the target object motion. On the basis of the OMR model, a dynamic IBVS method (i.e., IBVS based on kinematics, dynamics, and actuators) is then proposed to replace the kinematic IBVS method (i.e., IBVS based only on kinematics) such that the effects of the OMR dynamics, actuators, and target motion can be accommodated by using the FISMC method. In particular, the proposed FISMC method for the IBVS of OMRs can eliminate the reaching phase to make the states remain on the sliding surface all the time and improve the transient performance significantly when compared with the existing methods. The robust stability of the overall system using the proposed system is demonstrated by Lyapunov stability analysis. Simulation results are also provided to show that where the kinematic IBVS achieves much degraded performance owing to the OMR dynamics and target motion, the proposed FISMC-based dynamic IBVS method compensates for these effects and achieve the satisfactory feature point tracking performance, verifying the effectiveness of the proposed method.
Keywords: Degraded performance; Feature point tracking; Fuzzy integral sliding mode control; Image based visual servoing; Lyapunov stability analysis; Omnidirectional mobile robot; Transient performance; Wheeled Mobile Robots (WMRs); Actuators; dynamic image-based visual servoing; fuzzy integral sliding mode control; omnidirectional mobile robot; target motion